Coin-Operated Public Electric Vehicle Charging Station with Solar Panels as the Energy Source (Universitas Muhammadiyah Yogyakarta, 2023)
Electric transport is becoming increasingly popular as another option to use environmentally friendly energy in the form of transport. To support the development of electric transport, efficient and accessible charging infrastructure is required. Public Electric Vehicle Charging Stations (SPKLU) have become a major part of supporting long-distance travel and reducing the impact of greenhouse gas emissions on the environment. To increase the availability of SPKLUs and expand accessibility for electric vehicle users, this research aims to design an innovative coin-based SPKLU system that also utilizes solar energy through solar panels. The station can have a smaller environmental effect and lower operating costs by employing solar energy as its primary source. The examination included a review of the economy as well. As a result, those in charge, business owners, and communities who want to promote the usage of electric vehicles find it to be a desirable alternative. As a result of this research, it was found that a full charge of a 20Ah battery only requires a coin of Rp 7000